FAKTOR PENENTU NILAI PERUSAHAAN - Rismawandi Rismawandi (MANAJEMEN, 2024)
The comparison between stock price and book value is a company value. The high value of the company is certainly an attraction for investors to invest their capital in the targeted company, indicating that the company has good prospects in the future. This study aims to determine the effect of company age, company growth, managerial ownership and profitability on a company value. The population is manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) in the 2017-2021 financial statements. The research sample was determined using a purposive sampling technique based on certain criteria and a sample of 10 companies was obtained. The analysis method in this study uses multiple linear regression assisted by the SPSS Ver.20 program. The results show that company age, company growth, and profitability do not affect a company value, while managerial ownership has a positive and significant effect on a company value